Efeito estimulatório da vancomicina sobre o crescimento e a atividade proteolítica de células planctônicas e sésseis de Trichosporon spp. - Sousa, José Kleybson de (2021)
Trichosporon sp. are opportunistic pathogens associated with cases of fungal infections in hospitalized immunocompromised patients. Although little is known about the dynamics of tricosporonosis, it is known that the formation of biofilms is an important factor in the infectious process. Because of the prevalence of bacterial infections in the hospital setting, empirical treatment with antibacterial is often employed. Among the antibacterial routinely used in the therapy of immunocompromised patients are vancomycin and β-lactam antibiotics. However, little is known about the action of these drugs in the modulation of the infection and the virulence factors of fungi, such as those of the genus Trichosporon. The objective of this study was to evaluate the effect of vancomycin, amoxicillin, cefepime and meropenem on planktonic growth, formation of biofilms and proteolytic activity of Trichosporon species. Initially, exposure of planktonic cells to antibacterial was evaluated by broth microdilution assay using strains T. asahii (n=3), T. inkin (n=7), T. coremiiforme (n=2), T. debeurmannianum (n=1), T. faecale (n=1), T. japonicum (n=2), T. loubieri (n=1), T. mucoides (n=1) e T. ovoides (n=2). The influence of the antibacterial was tested on the adhesion of the strains of T. asahii (3) and T. inkin (7) to the polystyrene plate and on the formation and mature biofilm of Trichosporon spp., using XTT reduction methods and violet crystal staining. The proteolytic activity of planktonic and sessile cells was evaluated after exposure to antibacterial. A statistically significant increase in planktonic growth and proteolytic activity was observed only when the strains of Trichosporon spp. were exposed to vancomycin at concentrations of 15, 30 and 60 μg/mL. As regards the proteolytic activity of T. asahii and T. inkin planktonic cells, an increase in activity after exposure to cefepime (386 μg/mL), meropenem (66 μg/mL) and vancomycin (60 μg/mL) was observed. In addition, the metabolic activity of T. asahii and T. inkin biofilms exposed to vancomycin at concentrations of 15, 30 and 60 μg/mL presented a significant increase. The biofilm biomass increase was observed after exposure to vancomycin at concentrations of 15 and 30 μg/mL. The proteolytic activity of sessile cells showed a significant increase after exposure to vancomycin at concentrations of 15, 30 and 60 μg/mL. Scanning Electron Microscopy images showed a biofilm composed of multiple layers of structurally dense long hyphae. In the images of Confocal Laser Scanning, a biofilm increase in the concentration of 60 μg/mL was observed, but with no statistically significant difference. The results suggest that vancomycin stimulates planktonic and sessile growth in vitro of Trichosporon spp., as well as promotes an increase in the proteolytic activity of these opportunistic pathogens.